Pelatihan Infografis Edukasi Untuk Siswa Madrasah Tsanawiyah Negeri 5 Tasikmalaya - Muhamad Reza Atqia; Maya Kurnia; Rifa Zakiah; Afia Daffa Dhiaulhaq Alawiah; Qonitah Shapwah Mardiyah (CV. Biha Cendekia, 2025)
Educational infographic training is a way to strengthen digital and visual literacy for students in today's information technology era. This activity was conducted at MTsN 5 Tasikmalaya with the aim of improving students' ability to convey information creatively, concisely, and engagingly through infographics. The training used a participatory approach, including providing materials, hands-on practice in creating infographics using design applications (such as Canva), and presentations of student work. The results showed that students were highly enthusiastic and able to produce educational infographics on themes such as health, the environment, and anti-bullying. In addition to improving digital skills, this training also fostered students' critical thinking and visual communication skills. This activity is expected to become an innovative learning model that can be implemented sustainably in madrasah environments. The ability to convey information visually is a crucial skill in facing the challenges of 21st-century communication. This infographic design training was implemented as an effort to improve the visual literacy and digital skills of MTsN 5 Tasikmalaya students. The activity was designed as an interactive workshop that combined theoretical material with hands-on practice using online graphic design software. Participants were trained to process data and information into communicative and engaging visual displays. Evaluation of the training results showed improved student understanding of creating effective infographic design elements and increased confidence in conveying educational messages. This training is a relevant learning innovation to support student competency development in the digital age.